The Richness of Vocal Ornamentation in Lagu Gedé: A Case Study of Nunung Nurmalasari’s Performance of "Sungsang” Song - Lusyana Lusyana; Toni Setiawan Sutanto; Rita Tila; Hasan Irfanul'Alim Maulana (OSTINATO: Journal of Music Study and Research, 2025)
This study investigates the richness of vocal ornamentation in the lagu gedé repertoire through a focused case study of Sundanese pesinden Nunung Nurmalasari’s performance of “Sungsang.” Within Sundanese vocal tradition, ornamentation constitutes a central expressive mechanism through which musical identity, stylistic continuity, and interpretative creativity are articulated. Employing a qualitative case study approach, the research analyzes audiovisual recordings sourced from the official Nunung Nurmalasari Official YouTube channel, supported by numeric transcription, document analysis, and interview data. Content analysis is applied to identify, categorize, and interpret ornamentation techniques in relation to melodic structure, laras, surupan, and formal design. The findings reveal eleven distinct vocal ornamentation techniques: eluk tungtung, geregel, ombak, galasar, golosor, leotan, besot, eur-eur, gedag, dorong, and beulit systematically integrated throughout the performance. These ornaments function not merely as melodic embellishments but as structural and expressive devices that shape phrasing, reinforce modal modulation, and preserve lyrical clarity amid dense melodic decoration. Several techniques emerge as stylistic hallmarks, reflecting Nurmalasari’s distinctive vocal identity and deep mastery of Sundanese singing practice. The study concludes that vocal ornamentation in “Sungsang” operates as a coherent expressive system embedded within lagu gedé aesthetics. Its findings contribute to musicological and ethnomusicological discourse on kepesindenan and offer pedagogical value for Sundanese vocal education. Future research is encouraged to extend comparative analysis across performers and repertoires to further elucidate stylistic diversity in Sundanese vocal traditions.